Performance of treating aquaculture effluent using PHBV/volcanic rock/pyrite synergistic - ZHANG Haigeng; WANG Fangying; CAO Xinyuan; SUN Yating; XU Zhongshuo; ZHANG Yulei* (能源环境保护)
In order to address the low nitrogen and phosphorus removal efficiencies caused by a low carbon-to-nitrogen ratio in aquaculture effluents, a biofiltration device based on the synergistic coupling of 3-hydroxybutyrate and 3-hydroxyvalerate copolymers (PHBV) with volcanic rock and pyrite was developed and evaluated for its efficacy in treating aquaculture effluents. Two groups of filter devices with different filler contents were designed. In column 1, the device was filled with 15 cm of pyrite, 15 cm of mixed filter media, and 5 cm of volcanic rock from top to bottom. In column 2, the device was filled with 10 cm of pyrite, 15 cm of mixed filter media, and 10 cm of volcanic rock. The effects of different filler mass ratios on the efficiencies of denitrification and phosphorus removal were analyzed. The results showed that the average removal rate of nitrate nitrogen reached 97.8% in column 2, significantly higher than that in column 1 (p<0.05). However, the average removal rate of phosphate was lower than that in column 2, with an average removal rate of only 35.0%. Increasing the mass ratio of volcanic rock improved the removal of nitrate, while increasing the mass ratio of pyrite improved the removal of phosphate. Simultaneous removal of nitrogen and phosphorus was achieved when the dissolved oxygen concentration ranged from 1.2 to 1.5 mg/L. In conclusion, the process of synergistic enhancement of PHBV with volcanic rock and pyrite can achieve the simultaneous removal of nitrogen, phosphorus and other nutrients in aquaculture effluent, providing a new idea and a new method for solving the problem of deep purification of aquaculture effluent.